A topsy-turvy world : short plays and farces from the Ming and Qing dynasties (Columbia University Press, 2023)
"The high literary Yuan zaju plays and Ming chuanqi plays are well-represented in English translation, but the slightly later short plays (sometimes also called zaju) of the late Ming and early Qing have been long looked down upon and ignored as pedantic closet drama. Research of recent decades has created a quite different image: whereas chuanqi plays tended to strictly conform to genre rules, these short plays offered a space for experimentation, not only in formal aspects, but also in terms of content. Short plays were very much the genre in which Ming literati displayed their daring originality, eccentric personality, and withering criticism of contemporary social conditions, as well as their outrageous wit. A representative selection of these short plays will fill an obvious gap, and the editors see a need for such a volume in courses"-- Provided by publisher.
Keywords: Chinese drama -- Ming dynasty, 1368-1644 -- Translations into English.; Chinese drama -- Qing dynasty, 1644-1912 -- Translations into English.; LITERARY COLLECTIONS / Asian / Chinese; Chinese drama; Chinese drama -- Ming dynasty; Qing Dynasty (China); 1368-1912; Electronic books.; Translations